The Impact of Service Quality, Prices and Consumer Trust on Interest In Goods Deliveri Services (Case Study of Local Expedition Company Service Users in Pontianak City) - Maisirata, Pasifikus (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to determine service quality, price and costumer trust in interest in goods delivery services at local expedition companies in the city of Pontianak. The population in this study were all existing users of local expedition company services and the sample was determined using the Purposive Sampling method. The form of research is a form of causality research with data collection techniques using questionnaires. The analytical method used in this research is the rating scale method which is processed on a computer using the SPSS version 25 program. Data testing is carried out using validity tests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity and autocorrelation), correlation tests, coefficient tests determination, multiple linear regression test, F test and t test. Based on the test results (Test F), it shows that the variables of service quality, price and customer trust influence consumer buying interest. Partial test results (t test) show that service quality does not influence costumer buying interest, but price and costumer trust influence interest in using the company's goods delivery services.